Management of Corruption Prevention in an Islamic Education to Build Superior Human Resources - Mesiono,; Aziz, Mursal (International Journal of Psychosocial Rehabilitation, 2020)
Islam as a teaching of value system covers all aspects of human life. Through Islamic Education as a conscious and planned effort to create an atmosphere of learning and learning process so that students actively develop their potential to have spiritual spiritual strength, self-control, personality, intelligence, noble character, and the skills needed by themselves, society and the nation. Islamic education, as one of the existing education systems in Indonesia, contributes to the realm of preventing bad behavior including corruption. Islamic education based on the Qur'an and Hadith is very rich in values that are taught in harmony with the principles of anti-corruption education as a preventive effort. The value of Islamic education will be maximum in preventing corruption and can build superior human resources through good management processes. In Islamic education is very thick the value of faith, the value of honesty, the value of justice and the value of firmness holds a promise. Among the values of Islamic education in accordance with the principles of accountability, transparency and policy oversight are expected to be a solution to preventing corruption to build superior human resources.